Penguatan Kapasitas Masyarakat Desa Keru melalui Edukasi Standar Pengemasan dan Pelabelan Produk Pangan Lokal - Made Gendis Putri Pertiwi Putri Pertiwi; Firman Fajar Perdhana; Ika Rachmayani; Emi Pertiwi; Dina Supriani; Muammar Bima Fahlevi; Iqlima Khaerunnisa; Ismi Asmawati; Muhammad Rizqi Alfian; Erika Yuliana Pratiwi; Hidayatun Nisa; Rozal Ilham; Nindya Farah Dilla Harpama; Muhammad Zikro (Pendidikan Matematika, FKIP Universitas Mataram, 2026)
The enhancement of the added value and competitiveness of local food products in Keru Village is constrained by a limited understanding of food packaging and labeling standards. The community service activity aimed to enhance the knowledge of the community in Keru Village, Narmada District, West Lombok Regency regarding the importance of proper food packaging and labeling in accordance with established standards to improve the competitiveness of local products. The activity involved 23 participants consisting of palm sap farmers and members of the PKK women’s group. The methods used included administering an initial questionnaire (pre-test) to assess participants’ prior knowledge, delivering material through interactive lectures, and administering a final questionnaire (post-test) to evaluate participants’ understanding after the activity. The pre-test and post-test data were then analyzed descriptively. The results showed a significant increase in participants’ knowledge, where pre-test scores were categorized as low to moderate, while post-test scores improved to a high category. This indicates that the community service activity was highly effective in enhancing participants’ understanding. Therefore, the activity successfully achieved its objectives and has the potential to encourage the community to produce food products with better packaging and labeling, thereby increasing their competitiveness in the market